Streamlining digital signal processing : (IEEE Press, 2007)
Reprints 28 articles originally published in IEEE signal processing magazine on digital filters, signal and spectrum analysis tricks, fast function approximation algorithms, signal generation techniques, and high-performance DSP techniques. Topics include high-speed square root algorithms, recursive discrete time sinusoidal oscillators, designing non-standard filters with differential evolution, turbocharging interpolated FIR filters, and generating rectangular coordinates in polar coordinate order.